Emerging technologies for miniature spectrometers and multispectral sensors - Crocombe, Richard A. (SPIE, 2023)
Portable spectroscopy has been a rapidly growing field, being the subject of an extensive review in 2018. In 2021, the whole field of portable spectroscopy and spectrometry, from the technologies and instruments, through to field applications, required a two-volume book to do it justice. Progress in this field continues apace, with ever-smaller instruments and devices. Developments in other fields of optics and photonics are fueling this, and this paper summarizes some of the newer technologies being applied, and the technologies that could potentially be applied in the near future. Multispectral devices can be produced in volume via semiconductor and optical coating techniques, at very low cost - less than $10 each. Silicon photonics and photonic integrated circuits (PICs), produced en masse using semiconductor manufacturing techniques, are the ideal next step. This spectroscopic miniaturization, and concomitant cost reduction, has reached the point where multispectral sensors can now be incorporated into ‘fitness’ products like smart watches and sports watches, and into ‘wearables’ like smart rings, providing the user with health information, with several groups claiming they are close to a wearable non-invasive (i.e., optical) blood glucose device.